If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 15 = 56 + -3x Reorder the terms: 15 + 3x = 56 + -3x Solving 15 + 3x = 56 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 15 + 3x + 3x = 56 + -3x + 3x Combine like terms: 3x + 3x = 6x 15 + 6x = 56 + -3x + 3x Combine like terms: -3x + 3x = 0 15 + 6x = 56 + 0 15 + 6x = 56 Add '-15' to each side of the equation. 15 + -15 + 6x = 56 + -15 Combine like terms: 15 + -15 = 0 0 + 6x = 56 + -15 6x = 56 + -15 Combine like terms: 56 + -15 = 41 6x = 41 Divide each side by '6'. x = 6.833333333 Simplifying x = 6.833333333
| (X-3)(x+3)=14 | | 5(m+3)=2mb+24 | | 2x^2-585x+1000=0 | | X-4x+8x-7x-5x=9-2-8 | | 2x^2-585+1000=0 | | 24x-2y=-1 | | X+8-4x+8x=7x+9+5x-2 | | 9-(1-3y)=48+y-(3-y) | | 2x-5/-45/4 | | x^2+7*x+29=0 | | (8x+5)-20x=x | | -5(2/3)=(2/3)-6(2/3)= | | -5*2/3= | | 2y-6+3x=0 | | -5(2/3)= | | 7x+5y-3x-8y=1 | | 18y+x=28-3y | | x*x-5=126 | | 2b+3a=1.4 | | X/2=-15=x/5 | | 7y+5=20 | | 4/18=5/x | | 100/x=y | | 22-3(x-2)=2(4+x) | | x+x+x-5y-y-3x= | | 12x+3=-2b-4 | | -4x-4x-7y= | | x^2+3x+4-sqrt(x^2+3x+6)=0 | | 8x^6=2x^2 | | 8x^6=4x^2 | | 3z+6x-5z+2x= | | x^2+3x+4=sqrt(x^2+3x+6) |